2002
DOI: 10.2527/2002.801196x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of blood flow through the mammary gland in lactating sows: methodological aspects1

Abstract: Two replicates of three multiparous crossbred Large White x Landrace lactating sows were used to develop a technique for the continuous direct measurement of the blood flow through the mammary gland using transit time ultrasound. Four to six days after farrowing, an ultrasonic transit time flow probe was implanted around the right external pudic artery in order to measure the short-term variations of mammary blood flow through this vessel in response to postural change (standing vs lying), meal distribution, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 24 publications
2
36
2
Order By: Relevance
“…injection of 20 IU of oxytocin and returned to pre-injection values 12 min after the start of milking. Thereafter, blood flow increased and reached a maximum value 22 min after the onset of milking (Renaudeau et al 2002). These authors suggested that the post-suckling increase in mammary blood flow could be related to the nursing event and/or the increase in milk synthesis in response to the decreased milk volume in the udder.…”
Section: Regulation Of Mammary Blood Flowmentioning
confidence: 97%
See 4 more Smart Citations
“…injection of 20 IU of oxytocin and returned to pre-injection values 12 min after the start of milking. Thereafter, blood flow increased and reached a maximum value 22 min after the onset of milking (Renaudeau et al 2002). These authors suggested that the post-suckling increase in mammary blood flow could be related to the nursing event and/or the increase in milk synthesis in response to the decreased milk volume in the udder.…”
Section: Regulation Of Mammary Blood Flowmentioning
confidence: 97%
“…The Fick approach offers the advantage of not requiring arterial mammary blood per se; hence, catheter placement for arterial infusion or blood sampling may be done in any arterial sites. However, in contrast to the direct flow probe approach (Renaudeau et al 2002), the Fick approach may only be used to determine long-term changes in blood flow (i.e., daily) as opposed to changes occurring in the short term (i.e., minutes). In contrast to Linzell et al's study (1969a), other studies (Trottier et al 1997;Nielsen et al 2002a,b;Guan et al 2002Guan et al , 2004a,b) applied Fick's law of diffusion to measurement of mammary blood flow using internal markers.…”
Section: Farmer Et Al * the Lactating Sow's Mammary Glands 197mentioning
confidence: 99%
See 3 more Smart Citations